Mexico since 1980 - Haber, Stephen H., 1957- (World since 1980., 2008)
From the Publisher: This book addresses two questions that are crucial to understanding Mexico's current economic and political challenges. Why did the opening up of the economy to foreign trade and investment not result in sustained economic growth? Why has electoral democracy not produced rule of law? The answer to those questions lies in the ways in which Mexico's long history with authoritarian government shaped its judicial, taxation, and property rights institutions. These institutions, the authors argue, cannot be reformed with the stroke of a pen. Moreover, they represent powerful constraints on the ability of the Mexican government to fund welfare-enhancing reforms, on the ability of firms and households to write contracts, and on the ability of citizens to enforce their basic rights.